PENGARUH PERBANDINGAN SUKROSA DAN SIRUP GLUKOSA SERTA KONSENTRASI SARI SENDUDUK BULU (CLIDEMIA HIRTA L.) TERHADAP MUTU HARD CANDY - Naibaho, Benika; Hutajulu, Mutiara Fatima; Pandiangan, Samse (Jurnal Visi Eksakta, 2021)
Hard candy is a solid and hard-textured snack, the main ingredients in the manufacture of hard candy are sucrose, water, glucose syrup, while the additives are flavor, coloring and acidifying. The ratio of the amount of sucrose and glucose syrup used in the manufacture of hard candy will determine the texture that is formed. In general, hard candy is only known as a source of calories and does not contain antioxidants. One type of plant that is rarely used is the fruit of Senduduk Bulu (Clidemia hirta L.), this fruit contains high levels of antioxidants that can ward off free radicals in the body. The aims of this research are to investigate the effect of sucrose and glucose syrup ratio and the addition of different concentrations of senduduk bulu extract on physicochemical and organoleptic properties of hard candy. This study used a Factorial Completely Randomized Design consisting of 2 factors, namely the ratio of sucrose and glucose syrup consisting of 3 levels (70%: 30%, 75%: 25% and 80%: 20%) and the concentration of senduduk bulu extract with 4 levels. (0%, 3%, 6%, 9%). The parameters observed were water content, reducing sugar, antioxidant activity, hedonic organoleptics (color, taste, and texture). The results concluded that the ratio of sucrose and glucose syrup had a significant effect on reducing sugars concentration (P< 0.05), and was very significant (P <0.01) on organoleptic (color, taste) but did not affect water content, and organoeptic texture of hard candy . The addition of senduduk bulu extract had a very significant effect (P <0.001) on water content, reducing sugar concentration, and organoleptics (color, taste, texture) on hard candy senduduk bulu. The hard candy formula most preferred by panelists based on the hedonic test was A1B4 treatment (the composition of the ratio of sucrose and glucose syrup 70%: 30% with 9% senduduk bulu extract). The average value of the panelists' preference level for the parameters of color 3.66, taste 3.54, texture 2.82 and the average value of the test results 1.98% water content, 6.26% reduction sugar and has a very strong antioxidant activity with IC50 value of 36.84 ppm. All analysis tests met the quality requirements of SNI3547.1: 2008 hard candy.